Risk factors of neonatal asphyxia on storm baby - Novita Dewi, Novita Dewi (Universitas Gadjah Mada, 2005)
Background: Neonatal asphyxia remains the main cause of neonatal mortality as well as permanent neurological abnormality. With informed consideration about risk factors, more than half fetuses who need resuscitation could be identified prior to birth.Objectives: The study was aimed to identify antepartum and intrapartum risk factors in neonatal asphyxia of full term babies.Study Design: Case control.Material and Method: Data were collected from medical record of babies hospitalized in Subdivision of Perinatology, Department of Child Health in Dr. Sardjito Hospital in January to December 2004. The risk factors of neonatal asphyxia were identified before and during delivery. Data were analized using chi square, bivariate and multivariate analysis.Results: In multivariate analysis, antepartum factor which increases the risk of neonatal asphyxia was small for gestational of age (SGA) baby (OR: 3,43; CI 95%: 1,81-6,53). Intrapartum factors that increased the risk of neonatal asphyxia were meconium stained of amnion fluid (OR: 49,02; CI 95%: 12,34- 143,67), prolonged second stage of delivery (OR: 9,73; Cl 95%: 3,99-23,99) and Caesarean section delivery with general anesthesia (OR: 8,62; CI 95%: 2,16-34,44).Conclusion: SGA baby, meconium stained of the amniotic fluid, prolonged second stage of delivery and Caesarean section delivery with general anesthesia increased the risk of neonatal asphyxia in full term baby.Key words: risk factors - neonatal asphyxia - aterm babies